Socioeconomic Position in Early Life and Childhood Cardiovascular Health Measures: An International Cross‐Cohort Study - Kavindi Gamage; Susanna Pätsi; Tong Chen; Kate Mooney; Sylvain Sebert; Naomi Priest; Toby Mansell; David Burgner (Journal of the American Heart Association, 2026)
Background Cardiovascular disease is socioeconomically patterned, and risk accrues from early life. Evidence in younger populations is scarce. We investigated the extent to which early life socioeconomic position is associated with cardiovascular health in children and adolescents, and the extent of mediation by body mass index. Methods We analyzed 5 longitudinal birth cohorts: BIS (the Barwon Infant Study; Australia; mean age 4.1 years; n=708); BiB (Born in Bradford; United Kingdom; mean age 9.3 years; n=4576); LSAC‐CP (the Longitudinal Study of Australian Children's Child Health CheckPoint; Australia; mean age 12.0 years; n=1874); NFBC1986 (the Northern Finland Birth Cohort 1986; Finland; mean age 16.0 years; n=9467); and ALSPAC (the Avon Longitudinal Study of Parents and Children; United Kingdom; mean age 17.8 years; n=4875). Exposures were neighborhood disadvantage, household socioeconomic position, and maternal education (in pregnancy/at birth). Outcomes were carotid intima‐media thickness, pulse‐wave velocity, blood pressure, and lipids (in childhood/adolescence). Results From age 12 years, children with lower socioeconomic position had worse cardiovascular health, adjusted for age, sex, and ethnicity. For example, LSAC‐CP 12‐year‐olds in the most disadvantaged neighborhoods had higher pulse‐wave velocity (β=0.1 m/s [95% CI, 0.03–0.2 m/s]; P =0.003) than those in the most advantaged, and NFBC1986 16‐year‐olds whose mothers had the lowest education levels had higher triglycerides (β=0.07 mmol/L [95% CI, 0.0–0.1 mmol/L]; P =0.04) than those whose mothers had the highest education levels. Hypothetically intervening on body mass index would reduce 12% to 100% of some cardiovascular health differences. Conclusions Associations between lower socioeconomic position and worse cardiovascular health are apparent from midchildhood. Prevention efforts should address intermediate mechanisms and upstream neighborhood, household, and maternal factors.